Improving the recycling rate of construction and demolition waste in Sweden - a reverse logistics perspective - Manjunath, Chandan; Umrigar, Frashogar (My University, 2017)
Sweden has been very successful in recent years in increasing energy recovery and reducing waste in the form of landfills. However, there is a great scope for improvement of the recycling rate of waste. The EU Waste Framework Directive (European Parliament and Council, 2008) requires all the countries within the EU to have achieved a minimum recycling rate of 70% for construction and demolition waste (CDW) generated, by 2020. The recycling rate of CDW in Sweden is currently 50-60%. Improving the reverse logistics of CDW could contribute greatly towards achieving this target. This thesis focuses on understanding the current state of identification, sorting, collection and logistics of CDW in Sweden, which is a part of the reverse logistics chain. Based on the current state analysis, some suggestions for improvement are given. In this thesis, interviews and surveys are conducted with various stakeholders within the CDW industry. The surveys and interviews along with the help of a literature review are used to understand the factors that affect the identification, sorting, collection and logistics of CDW. Additionally, five cases of construction/demolition projects are studied. The analysis of the data collected in term of five case studies, interviews and a survey, has supported in answering the purpose. Based on the current state of operations and the factors affecting them, some suggestions for the improvement are provided. The suggestions are – i) using the waste management plan throughout the chain, ii) improving the waste management plan and iii) using additional waste coordinators on-site. Application of these suggestions could lead to improvements in the reverse logistics of CDW and help in increasing the recycling rate of CDW in Sweden.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other industrial engineering and economics